UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA 4-5 TAHUN MELALUI STRATEGI BERMAIN STICK ANGKA DI PAUD AL MUBAROKAH DESA MAKMUR SEJAHTERA KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR - Lilik Suryandari; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study was conducted in early childhood Al Mubarokah Desa Makmur Sejahtera Kec. Gunung Sahilan. The school is located approximately 80 km from the capital of Kampar regency, Riau Province. This research was conducted at the school due to lack of numeracy among children aged 4-5 years. For the class was chosen as a place to study. Application of stick figures to improve numeracy initial 4-5 year olds conducted in groups. Each cycle exercisable three times and gained 73.8% in value. Thus researchers did not continue to the next cycle. So playing stick figure can increase a child's ability to count starting at the age of 4-5 years early childhood Al-Mubarikah Makmur Sejahtera District Sahilan Kampar regency. Activity bet stick figures in the first cycle and the second meeting I and II play stick figures mentioned by the 1-10 sequentially properly, breaks down the numbers as instructed teachers, learn concepts and a lot of little things, recognize the concept of number, and count the number of have been grouped. That play with stick figures can improve numeracy initial 4-5 year olds in pre-school Al-Mubarikah Makmur Sejahtera District Sahilan Kampar regency. Percentage increase in numeracy initial 4-5 year olds by playing strategy stick figures in Al-ECD Mubarokah Makmur Sejahtera District Sahilan Kampar is 41.3% from the first cycle to the second cycle and 90.7% from the previous cycle to cycle.Keywords: Beginner Numeracy Strategy Play Stick Figures